Globalization, State, Identity/Difference: Toward a Critical Social Theory of International Relations by E. Fuat Keyman. Atlantic Highland: New Jersey, Humanities Press, 1997, 224pp. (American Journal of Islam and Society, 1998)
What is reality? Is reality what we see? How do we tell what is real, and how do wedifferentiate “real” from “false” or uncover the truth in an objective fashion? The searchfor reality or understanding the dynamics of human interaction in an institutionalized settinghas resulted in a vibrant debate in international relations (IR) theory over the metatheoreticalfoundations of knowledge production. Positivists and realists claim that truth andreality can be and have been uncovered by thorough and patient research. Truth is, after all,“out there” somewhere in the real world, and it is the task of social scientists to uncover it.Critical social theorists, however, argue that social science is not akin to physical or evennatural sciences, for human behavior is dynamic and varies both spatially and temporally.“Reality” or “truth” can never be discovered or known completely because of the nature ofsocial activity. Furthermore, there are no fixed foundations for judging what is “real,”“true,” or “false.” Hence, the attention of critical social inquiry has focused predominantlyon the epistemological and ontological foundations of social scientific methods.By concentrating on epistemology and ontology, critical social theorists have shownthe structural weakness of positivist and realist theories. Furthermore, the inability of positivesocial science to go beyond surface structures to explore deep structures of knowledgealso has been exposed by critical social theorists. The unequivocal outcome of critical socialtheory is that knowledge, interest, and preference matter and, therefore, cannot be assumed.The critical social theorist does not focus on the cognitive manifestations of knowledge,interests, and preferences, but rather on how they are formed, created, or constructed.However, despite its ombudsman-like value and importance, critical social theoryhas yet to emerge as an effective alternative to positive social science. Critical social theoryhas remained true to its name and has continued to play the role of a harsh but valuablecritic. Keyman seeks to buck this trend by providing a basis for using critical socialtheory not just as an epistemological critique to challenge the extant theoretical hegemony,but also to deploy it as a “first-order theorizing tool”-an ambitious goal indeed. Hisbook is an attempt to bridge the theory-metatheory gap found in IR theory and, at the sametime, elevate critical social theory to the level of such first-order theories as the muchmaligned Waltzian theory of international relations. The challenge of deploying criticalsocial theory not just as a captious force, but rather as a constructive theory, is a difficultand slippery task. Critical social theory should be able to criticize and dismantle withoutrelying on foundational support (i.e., without relying on positivistic moments). In addition,it also should resist succumbing to the temptation of assuming the discourse of thehegemon, in which the “other” becomes the subject.Keyman attempts to traverse these intellectual minefields by emphasizing the need fordialogical interaction between discourse (object) and subject. The object and subject should ...